2023
DOI: 10.1002/mp.16407
|View full text |Cite
|
Sign up to set email alerts
|

Need for objective task‐based evaluation of deep learning‐based denoising methods: A study in the context of myocardial perfusion SPECT

Abstract: Background Artificial intelligence‐based methods have generated substantial interest in nuclear medicine. An area of significant interest has been the use of deep‐learning (DL)‐based approaches for denoising images acquired with lower doses, shorter acquisition times, or both. Objective evaluation of these approaches is essential for clinical application. Purpose DL‐based approaches for denoising nuclear‐medicine images have typically been evaluated using fidelity‐based figures of merit (FoMs) such as root mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…However, imaging algorithms, including those based on DL, are often evaluated using figures of merit (FoMs) that are not explicitly designed to measure clinical task performance ( 11 ). Recent studies conducted specifically in the context of evaluating image-denoising algorithms showed that task-agnostic FoMs may yield interpretations that are inconsistent with evaluation on clinical tasks ( 13 17 ). For example, in Yu et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, imaging algorithms, including those based on DL, are often evaluated using figures of merit (FoMs) that are not explicitly designed to measure clinical task performance ( 11 ). Recent studies conducted specifically in the context of evaluating image-denoising algorithms showed that task-agnostic FoMs may yield interpretations that are inconsistent with evaluation on clinical tasks ( 13 17 ). For example, in Yu et al.…”
mentioning
confidence: 99%
“…For example, in Yu et al. ( 17 ) a DL-based denoising algorithm for myocardial perfusion SPECT indicated significantly superior performance based on a structural similarity index measure and mean squared error but did not yield any improved performance on the clinical task of detecting myocardial perfusion defects.…”
mentioning
confidence: 99%